Breaking the Limitations of Sulfur Redox Kinetics by Accelerated Li+-Desolvation in Lithium–Sulfur Batteries - Wang, Tan; Wang, Zhenhua; Gao, Xiaotian; Bai, Zhe; Liu, Wanning; Bai, Yu; Rooney, David; Sun, Kening (Nano-Micro Letters, 2026)
The practical deployment of lithium–sulfur batteries (LSBs) is fundamentally limited by the sluggish stepwise sulfur redox kinetics. However, current design philosophies remain heavily constrained by the conventional “adsorption-catalysis” strategy, often overlooking the crucial rate-limiting kinetic obstacle of the high Li+ desolvation energy barrier. This sluggish Li+ desolvation process imposes a severe kinetic penalty on polysulfide conversion, thereby depressing electrochemical stability. Herein, we propose a catalyst desolvation strategy utilizing a Ce single-atom catalyst to promote the Li+ desolvation process, thereby enhancing the redox conversion of polysulfides. Results indicate that the catalyst desolvation strategy increases the proportion of contact ion pairs and aggregates, reduces the Li+ desolvation energy barrier, and stabilizes the lithium anode/electrolyte interface. Consequently, the accelerated Li+ desolvation facilitates rapid sulfur redox kinetics, thereby realizing stable cycling in LSBs with a low decay rate of 0.036% per cycle over 1700 cycles at 1 C. This work confirms the significant impact of Li+ desolvation and provides a new solution for achieving efficient conversion of polysulfides in LSBs. Highlights: 1 A catalyst desolvation strategy via phosphorus-modulated Ce single-atom catalysts is proposed to reduce the Li+ desolvation barrier and accelerate reaction kinetics. 2 The Ce-f orbital achieves a maximized overlap with the S-p orbital, and this strengthened f-d-p orbital hybridization effectively inhibits the diffusion of polysulfide anions through the interlayer. 3 Synergizing accelerated Li+ desolvation with suppressed polysulfide shuttling, the batteries demonstrate ultrastable cycling with an ultralow decay rate of 0.036% per cycle over 1700 cycles.